Biomass production and nutrient accumulation and release by cover crops in the off-season - Pacheco, Leandro Pereira; Leandro, Wilson Mozena; Machado, Pedro Luiz Oliveira de Almeida; de Assis, Renato Lara; Cobucci, Tarcísio; Madari, Beáta Emoke; Petter, Fabiano André (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to evaluate the performance of cover crops regarding biomass production and nutrient accumulation and release during the off-season in a clayey Red Latossol (Ferralsol) in the Cerrado. The assay was carried out at Santo Antônio de Goiás and Rio Verde, GO, Brazil from November/2007 to October/2008. A randomized block design in a split-plot arrangement in time was used, with the cover crops evaluated in the main plot and with biomass sampling time in the subplot, with four replicates. The evaluated species were: Urochloa brizantha, U. ruziziensis, Pennisetum glaucum e U. ruziziensis + Cajanus cajan and, as reference, a fallow treatment with spontaneous vegetation. Sampling times were six in Santo Antônio de Goiás and five in Rio Verde, since the desiccation date of P. glaucum, 60 days after cover crop sowing. P. glaucum showed the largest quantities of dry biomass at the beginning of the off-season, while the other covers showed significant accumulations of biomass and nutrients at the end of the off-season.